Constructing the Internal Enemy: A Discouse Analysis of the Representation of Islam and Muslims in Bosnian Media - Karčić, Harun (Context: Journal of Interdisciplinary Studies, 2022)
This paper analyses five major Bosnian daily newspapers over a period spanning from August 1st, 2018 until August 2019 ,31 and attempts to discern the main patterns in the discourse over Muslims and Islam in Bosnia and Herzegovina. The results of this research show three major discursive patterns when covering Muslims and Islam in the country: Bosnian Muslims as political obstructionists; Bosnia and Herzegovina as a haven for Muslim extremists and finally Muslim migrants as a threat to the country and to Europe.